Disciplining Otherness in Female-Authored Bildungsromans - Sabaté Planes, Dolors (Tropelías: Review of Literary Theory and Comparative Literature, 2025)
The Bildungsroman reveals a heteropatriarchal and Eurocentric ideological substratum, upon which the educational ideal conceived during the Enlightenment is founded. Our analysis highlights the fact that the Bildungsroman, as a literary genre with didactic intentions, participates in the processes of disciplining otherness. In the case of Bildungsromane produced by female writers, these works both document and shape the bourgeois discourse on gender by reproducing disciplinary processes. To illustrate these ideas, we will examine the evolution of the Bildungsroman and turn to Grete von Urbanitzky's work, Eine Frau erlebt die Welt. This text serves as a clear example of how the Bildungsroman, even when written by women, not only documents but also contributes to the construction of the Eurocentric and heteropatriarchal bourgeois discourse on gender and culture.
Keywords: Bildungsroman; Women Writers; Interwar German Literature